PENERAPAN ARTIFICIAL FISH SWARM ALGORITHM (AFSA) PADA MULTIPLE TRAVELLING SALESMAN PROBLEMS (m-TSP) - Fismaya, Florencia Wahyu Ganda; Riski, Abduh; Kamsyakawuni, Ahmad (Majalah Ilmiah Matematika dan Statistika, 2020)
Selling or trading in the industrial 4.0 era as it can now be done by opening a shop online. Therefore, shopping at this time can also be done online also, so that the online shop owners require orders that do not allow for Cash On Delivery (COD) transactions using package delivery services. This research discusses about finding a solution for good shipping with a minimum total mileage of several couriers at PT. Titipan Kilat District Banyuwangi uses AFSA as a settlement algorithm. The experimental process is carried out by using several parameter values to determine the parameters that affect the final solution. Each parameter will be tested with a maximum of 1000 iterations, then the best results will be tested again with a maximum iteration of 2000, and 5000 and will be compared with the original distance traveled by the couriers. The final solution offered in the form of a delivery route by three couriers with the total distance (Z) of the third courier is 87.28 Km with the smallest iteration value reaching the local minimum in iteration 1169. Keywords: artificial fish swarm algorithm (afsa), multiple travelling salesman problem (m-tsp), route, total mileage.